2014
DOI: 10.1080/13554794.2014.969277
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment following right cerebellar infarction: a case study

Abstract: We reported a patient with a right cerebellar infarction who showed anterograde amnesia. Cognitive dysfunction caused by cerebellar lesions was called cerebellar cognitive affective syndrome, and deactivation of the contralateral prefrontal cortex function due to disconnections of cerebello-cerebral fiber tracts have been hypothesized as mechanism underlying the syndrome. The episodic memory impairment, however, could not be supported by the same mechanism because the prefrontal lesions cannot cause amnesia sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Single-photon emission computed tomography (SPECT) revealed insufficient perfusion in the right cerebellar hemisphere and the left frontotemporal area, including the left prefrontal lateral cortex, with slightly reduced perfusion in the left anterior thalamus. The authors suggested that the memory impairment was linked to the thalamus, which acts as a relay station in the complex network of cerebellar-brain connections (Nakamoto et al, 2015).…”
Section: Cerebellum and Working Memorymentioning
confidence: 99%
“…Single-photon emission computed tomography (SPECT) revealed insufficient perfusion in the right cerebellar hemisphere and the left frontotemporal area, including the left prefrontal lateral cortex, with slightly reduced perfusion in the left anterior thalamus. The authors suggested that the memory impairment was linked to the thalamus, which acts as a relay station in the complex network of cerebellar-brain connections (Nakamoto et al, 2015).…”
Section: Cerebellum and Working Memorymentioning
confidence: 99%
“…The executive function deficits include short-term memory impairments and an inability to learn new information. Nakamoto et al (2015) reported an interesting case of a gentleman with a stroke in the cerebellar vermis and superior right cerebellum along with SPECT showing hypoperfusion of the right hemicerebellum and the left anterior thalamus. The individual developed episodic memory impairment with largely preserved working memory that eventually improved after 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, several functional neuroimaging studies have confirmed that the cerebellum, especially the PCL, plays an important role in higher‐order functions other than motor coordination and motor learning, including working memory (Durisko & Fiez, ; Hautzel, Mottaghy, Specht, Müller, & Krause, ), episodic memory (Fliessbach, Trautner, Quesada, Elger, & Weber, ; Spaniol et al, ), and executive functions (Stoodley, ; Stoodley & Schmahmann, ; Stoodley, Valera, & Schmahmann, ). Executive control, episodic memory, and linguistic abilities would be impaired if the PCL were damaged (Nakamoto, Tsutsumiuchi, Maeda, Uesaka, & Takeda, ; Schmahmann, ; Tamagni et al, ). In addition, the cerebellum shows age‐related declines in structural morphology and function, which lead to a decline in cognitive behaviors in older adults (Bernard & Seidler, ; Jacobs et al, ).…”
Section: Discussionmentioning
confidence: 99%